Scalp Myiasis Associated with Advanced Basal Cell Carcinoma - Ali Asilian; Fateme Andalib (مجله دانشکده پزشکی اصفهان, 2012)
Background: Myiasis is a term derived from the Greek word ‘‘myia’’ which means fly. The flies deposit their eggs, which then hatch into larvae, which in turn infiltrate the tissue and destroy it. This disease is generally associated with traumatic injury, erosive or ulcerative lesions, or hemorrhage. However, the association with basal cell carcinoma has been extremely rare. Case Report: The patient is a 64-year-old woman, widow, living in a rural area, who was accompanied by her neighbour to the dermatology clinic. There is a large ulcerative and hemorrhagic area on the scalp which in some parts is covered by larvae (arrowheads). She did not suffer any pain but it smelled foul. Miyasis was treated by mechanical removal. The biopsy of the ulcerated area confirmed the diagnosis of basal cell carcinoma and the patient was referred to a plastic surgeon for resection and graft. Conclusion: It is said that incidental finding of myiasis may be actually of some benefit to the patient. The natural debridement performed by the larvae helps to keep the amount of necrotic tissue and the infection at a minimal level.